The impact of nickel and chrome mine tailings on the growth of Hibiscus cannabinus and Linum usitatissimum and a preliminary assessment of their applicability as economically beneficial phytoremediation species - Campbell, Tiago Roberto (University of the Witwatersrand, Johannesburg, 2023)
Current and previous mining activities in South Africa have caused various environmental, human health and societal impacts. This has led to the formation and enforcement of legislation regarding the rehabilitation of active, closed and abandoned mines in South Africa. The requirements contained in this legislation include rehabilitation, skills transfer, job creation and development of post mine land use regarding active, closed and abandoned mines. A common impact of mining activities is the contamination of soils with various metals. The process of phytoremediation has demonstrated potential in the remediation of metal contaminated soils. Plant species commonly utilised in this process are hyper accumulators, which can translocate and accumulate high concentrations of various metals from soils into their biomass. However, large areas of previously economically productive land become underutilised when hyper-accumulators are used for phytoremediation. Economically valuable fibrous plant species have demonstrated potential in their use as phytoremediation species. This presents an opportunity in which economically valuable plant species could be utilised in phytoremediation applications on active, closed and abandoned mines in South Africa. Thus, the aim of this research was to assess the ability of Hibiscus cannabinus and Linum usitatissimum to grow in and extract metals from soil contaminated with nickel and chrome mine tailings. Furthermore, the concurrent use of H. cannabinus and L. usitatissimum as phytoremediative and economically beneficial plant species was determined. Normal (non impacted), rehabilitated (previously impacted) and tailings (impacted) soil treatments were collected and used from the Onverwacht tailings storage facility of Nkomati Nickel mine. Hibiscus cannabinus and L. usitatissimum were cultivated in each soil treatment in greenhouse conditions over a six-month period. Multiple plant growth parameters were recorded at monthly intervals. The amount (mg) and concentration (mg/kg) of Mn, Zn, Ni, Cu, Cr and Co contained within plant tissue samples at the end of the six-month period was determined. The area (ha) of land categories available for H. cannabinus and L. usitatissimum cultivation onsite was determined using Sentinel 2B satellite imagery and supervised image classification. The measured and expected total yield (t), yield value (R), profit/loss margin (R) and amount (g/ha) of Mn, Zn, Ni, Cu, Cr and Co extracted through cultivation of H. cannabinus and L. usitatissimum onsite was determined. The growth of H. cannabinus and L. usitatissimum cultivated in rehabilitated soil was severely impacted. While growth of each species exhibited minimal differences between those cultivated in normal and tailings soil. Hibiscus cannabinus consistently exhibited greater growth than L. usitatissimum. Both species demonstrated the ability to accumulate varying amounts and concentrations of each of the tested metals in their total, above and below ground components. Both species consistently accumulated increased amounts and concentrations of Mn and Zn. Those cultivated in tailings soil exhibited increased accumulation of Cr. Linum usitatissimum generally accumulated metals at higher concentrations than H. cannabinus, however, minimal differences in the amount of metal accumulated between species were observed. Based on the measured yield cultivation of each species onsite would result in economic loss and generally low metal extraction. However, based on the expected yield, species cultivation onsite, in normal and tailings soil, would result in economic gain and generally high metal extraction. Hibiscus cannabinus and L. usitatissimum exhibited phytoremediative and economic potential. Aspects of the current state of mine impacted land in South Africa and the requirements of rehabilitation enforced through South African legislation could possibly be addressed through the application of H. cannabinus and L. usitatissimum for mine rehabilitation strategies.
A dissertation submitted in fulfilment of the requirements for the degree Master of Science, to the Faculty of Science, School of Animal, Plant and Environmental Sciences, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Phytoremediation; Hibiscus cannabinus and Linum usitatissimum; Nickel and chrome mine tailings; Supervised image classification; Economic value; UCTD; SDG-13: Climate action